Involvement of Frontal Functions in Pain Tolerance in Aging: Evidence From Neuropsychological Assessments and Gamma-Band Oscillations - Zhou, Shu; Lithfous, Ségolène; Després, Olivier; Pebayle, Thierry; Bi, Xiaoying; Dufour, André (Frontiers in Aging Neuroscience, 2020)
Reduced pain tolerance may be one of the possible explanations for high prevalence of chronic pain among older people. We hypothesized that age-related alterations in pain tolerance are associated with functioning deterioration of the frontal cortex during normal aging. Twenty-one young and 41 elderly healthy participants underwent a tonic heat pain test, during which cerebral activity was recorded using EEG. Elderly participants were divided into two sub-groups according to their scores on executive tests, high performers (HPs; n=21) and low performers (LPs; n=20). Pain measures (exposure times (ET) and perceived pain ratings) and cerebral activity were compared among the three groups. ETs were significantly lower in elderly LPs than in young participants and elderly HPs. EEG analyses showed that gamma band oscillations (GBOs) were significantly increased in pain state for all subjects, especially in the frontal sites. Source analysis showed that GBOs increase in elderly LPs was contributed not only by frontal but also by central, parietal and occipital regions. These findings suggest that better preservation of frontal functions may result in better pain tolerance by elderly subjects.